Frequency and spectrum of cutaneous metastases of visceral malignancies: A retrospective observational study of three years duration in a tertiary care hospital - Vandana Rana; Kanchan Kulhari; Disha Dabbas; Harish S Murthy; Puneet Takkar (Wolters Kluwer Medknow Publications, 2021)
Background: In spite of the skin being the largest organ of the body, cutaneous malignancies are uncommon especially in people of color as compared to the white population. The incidence of cutaneous metastases of visceral malignancies is further low and accounts for 0.5% to 10% of cancer cases as per written literature. Cutaneous metastasis as the presenting sign of underlying internal malignancy is extremely rare and is a marker of poor prognosis. Limited data is available in written literature about the frequency and spectrum of metastatic skin lesions in the Asian population. Objective: 1) To find the frequency of metastasis of visceral malignancies in skin biopsies. 2) To evaluate the clinicopathological presentation and immunohistochemistry (IHC) profile of cutaneous metastases. Subjects and Methods: It is a retrospective analysis of all the skin biopsies received in our department of Pathology for HPE from 01 Jan 2017 till 31 Dec 2019. Cases of cutaneous malignancy were segregated into primary and metastatic categories. Clinical details of the cases of cutaneous metastases were retrieved and analyzed. All the cases of cutaneous metastases were studied in detail for their clinical presentation, histomorphological features, and findings on IHC. Results: Out of a total of 484 skin biopsies in 3 years, 9.7% showed features of malignancy. Total ten cases of cutaneous metastases (2%) were found, out of which three were the primary presentation of silent visceral malignancy. The lung, breast, colon, and ovary were the common primary sites to manifest as cutaneous metastases with the abdominal wall being the commonest site. Histomorphological features aided by the IHC panel helped in diagnosing the cutaneous metastases and site of the primary malignancy. Conclusion: Cutaneous metastasis as the primary presentation of visceral malignancy is rare and should not be missed as it indicates a poor prognosis. Clinico-pathological correlation and histomorphological features assisted by IHC markers help pathologists in diagnosing the site of primary malignancy in cases of cutaneous metastases.